Formulation and Evaluation of Oral Disintegrating Tablets of Lamotrigine Solid Dispersions: Oral dispersible tablets - P.K.Lakshmi; Swetha Reddy; C. Kishore; Satish Reddy (Iranian Journal of Pharmaceutical Sciences, 2013)
Lamotrigine is used in the treatment of CNS disorders, particularly epilepsy; pain; oedema; multiple sclerosis and psychiatric indications including bipolar disorder. Lamotrigine belongs to biopharmaceutical classification systems; BCS class II (Low solubility & High permeability). In addition, it requires immediate therapeutic action. Hence, the main objective of this study is to improve the solubility by solid dispersion technique and formulate it as oral disintegrating tablets (ODT) to avert the problems of swallowing and to provide rapid onset of action. Lamotrigine solid dispersion was prepared by using Tween 80 and Gelucire 44/14 as solubility enhancers and formulated it into ODT by direct compression technique using different concentrations of Kyron T-314, Kyron T-154, and Kyron T-104 as cross linked polymers. The tablets were evaluated for various parameters and the results were found to be satisfactory. The batches of LMTK314 (2), LMGK314 (2) were selected as optimized batch containing Kyron T-314 as super disintegrant in 2% concentration, as they showed 100% drug release in 8 minutes and 6 minutes with a disintegration time of 11 and 9 seconds respectively. Upon comparison of dissolution profiles of optimized formulae LMTK314 (2), LMGK314 (2) with a marketed product, it proved that the optimized formulae had shown better dissolution. The optimized formulations were subjected to stability studies for three months as per ICH guidelines and showed physical stability with insignificant change in the hardness, disintegration time, drug content and in vitro drug release.